Parque Natural da Arrábida e Área de Paisagem Protegida do Sudoeste Alentejano - Caeiro, Sandra (1997)
In this section a general characterization of the coastal arca of the Parque Nacional da Arrábida (PNA) is given. The Parque Nacional da Arrábida located in the most southern part of de Setúbal peninsula, occupies an area of 10.800 Ha. Geographically the PNA is placed between the parallels 38° 27"- 38° 38'northlatitude and 8°55" - 9° 50' longitude west (Trindade, 1988). The area contains a small chain of limestone outcrops with a maximum elevation of S00 m running parallel to the southern cdge of Setúbal peninsula, ending in steep cliffs rising from the sea. (Catarino er al., 1981).